Partners in discovery: building equal and proactive patient engagement in inflammatory myopathies - Karen Cheng; Valérie Leclair (Current Opinion in Rheumatology, 2026)
Purpose of review Patient engagement in research has evolved from passive participation and inclusion toward active partnership and co-leadership. This review examines the current landscape of patient involvement in myositis research, highlights existing initiatives and frameworks, and identifies persistent gaps and overlaps. Recent findings In myositis, or inflammatory myopathies, early onboarding and integration of patients as research partners in preclinical and clinical studies offer invaluable opportunities to improve relevance, feasibility, and impact of research. The findings presented emphasize the importance of early partnership with patient research partners (PRPs), bidirectional training to foster mutual understanding, and expanded outreach to underrepresented regions. Summary Patient engagement in myositis research has advanced considerably, yet its integration remains inconsistent worldwide. Several existing resources can be leveraged to facilitate patient engagement in myositis research, but achieving meaningful PRP integration requires deliberate effort, adequate resources, and a commitment to cultural change.